Розробка багатопотокових мобільних додатків інформаційно-навчального призначення - Сав'юк, Лариса Олександрівна; Іванів, Роман Богданович (НТУ "ХПІ", 2016)
Розглянуті підходи до застосування мобільного навчання в системі освіти, визначена сутність мобільного навчання, його співвідношення з дистанційним й електронним навчанням, а також окреслені його переваги і недоліки. Запропоновано моделі впровадження мобільного навчання в навчальний процес вищих навчальних закладів. Наведений опис розробленого мобільного додатку інформаційно-навчального призначення, який націлений на інтеграцію мобільних технологій в організацію навчального процесу кафедри Інформаційно-телекомунікаційних технологій та систем інституту інформаційних технологій Івано-Франківського національного технічного університету нафти і газу.

The approaches to the use of mobile learning in the education system, defines the essence of mobile learning and its relationship to the distance and E-learning, as well as outlines its advantages and disadvantages. The article proposes a model of mobile learning implementation in the educational process of higher educational institutions. The description of the developed mobile application of information and educational purposes that is aimed at the integration of mobile technologies in the educational process of the department of information and telecommunication technologies and systems Institute of Information Technologies of Ivano-Frankivsk National Technical University of Oil and Gas. Scientific innovation is the development of mobile learning application that implements the principles of openness higher education – flexibility, modularity, independent of time and place, the use of modern information and communication technologies. In developing the application included didactic principles – multimedia, interactivity, accessibility. The practical significance of the development is to use a lot of threading tasks in the operation of a mobile application. This separation leads to more efficient use of resources and mobile networks of educational institutions. The main advantage of this mobile application is the ability to download educational content using cloud directly to your mobile device using multithreading technology, namely NS Operation Queue and Core Data framework for storage.
Developing multithreaded applications of mobile information and educational purpose
Keywords: інформаційно-комунікаційні технології; освіта; вищий навчальний заклад; дистанційне навчання; мобільне навчання; мобільний додаток; багатопоточність; ICT; education; higher education institution; distance learning; E-learning; mobile learning; mobile application; multithreading